Pengaruh Pendidikan Kesehatan Audio Visual Terhadap Pengetahuan Lansia dengan Hipertensi di Puskesmas Sukajadi Kabupaten Banyuasin: Penelitian - Yora Nopriani; Kuzwani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
According to WHO data, hypertension, or high blood pressure, affects approximately 1.28 billion adults aged 30–79 years worldwide, and about 6–15% of cases occur in the elderly population. One effort to improve knowledge about hypertension among the elderly is by providing direct health education or counseling using audiovisual media. This study aimed to analyze the effect of audiovisual health education on the knowledge of elderly people with hypertension at Sukajadi Public Health Center, Banyuasin Regency. This study used a quasi-experimental method with a one-group pre-test post-test design approach. The population consisted of all elderly individuals at Sukajadi Public Health Center, Banyuasin Regency, from January to April 2025, with a total sample of 54 respondents. The sample was selected using purposive sampling based on inclusion and exclusion criteria. The results showed that before receiving audiovisual health education, 35 respondents (64.8%) had poor knowledge, and after the education, only 9 respondents (16.7%) still had poor knowledge. Statistical test results indicated that audiovisual health education had a significant effect on the knowledge of elderly people with hypertension at Sukajadi Public Health Center, Banyuasin Regency, with a p-value = 0.000.